Species identification of felis and vulpes by a novel loop-mediated isothermal amplification assay in fur products. (January 2019) - Yu, Shunji; Gu, Wenjia; Yu, Yi; Qu, Qinfeng; Zhang, Yi'nan
In the chaotic market of fur goods, genetic distinction is increasingly important for identifying species. A vast diversity of species identification methods has been proposed, while little is developed, particularly those easy, fast, and cost-effective ones. In this study, a simple and reliable novel loop-mediated isothermal amplification method for identifying cytochrome c oxidase I of felis and vulpes was established. It saves laborious post–polymerase chain reaction procedures and shortens the time for high-fidelity gene amplification. The sensitivity of this method for felis and vulpes identification, which is well matched to quantitative polymerase chain reaction, could be 10 or 1.0 pg, respectively. Predominantly, the sensitivity of loop-mediated isothermal amplification is more tolerant to those polymerase chain reaction inhibitors such as pigments, dyes, or other fur ingredients, compared to quantitative polymerase chain reaction. Even without costly specialized equipment, a water bath is sufficient for genetic distinction. Our approach is a new technique with broad application perspective, such as on-site species identity tests, commercial fraud, and wildlife crimes.